Meningkatkan Motivasi Siswa Melalui Penerapan Small Sided Games - Mochamad Ridwan (UIR Press, 2020)
Students feel bored when the teaching approach is monotonous and unchanging, making it essential for Physical Education, Sports, and Health (PJOK) teachers to provide variations in the learning process. Therefore, this study aims to determine student motivation in football material by implementing small-sided games. A descriptive and quantitative research method with a school survey approach was employed, while the data was collected by using questionnaires distributed to 49 students. Then, data analysis was performed by using descriptive statistics in the editing, coding, and scoring stages. The results showed that two and four students had 4.1% and 28.6%, meaning they had very low and low motivation to follow the football material. Eighteen students scored 36.7%, nine had 18.4%, while six scored 12.2%, which means they had sufficient, high, and very high motivation. Therefore, the study results concluded that giving small-sided games made students' motivation to follow football material more suitable. Furthermore, a study with more extensive and varied sample sizes was recommended to discover other solutions to the problem.